ANALISIS PENERAPAN AKAD MUDHARABAH DALAM PRODUK TABUNGAN HAJI DAN UMROH PADA BTN SYARIAH KCPS KUDUS - Rokmah, Fadilatur; Wahidullah, Wahidullah; Mubarok, Ahmad Fauzan (Borneo : Journal of Islamic Studies, 2025)
Islamic banking in Indonesia has experienced significant growth, driven by increased public awareness, supportive regulations, and product innovations such as hajj and umroh savings. This study analyzes the application of the mudharabah contract in hajj and umroh savings products at BTN Syariah KCPS Kudus, focusing on compliance with sharia principles and economic effectiveness. Employing a qualitative approach through interviews, observations, and documentation, the study finds that the applied mudharabah muthlaqah contract complies with the DSN-MUI Fatwa, with a profit-sharing ratio of 45:55 and fund management through sharia-compliant instruments. However, low customer literacy and lack of transparency in fund management pose significant challenges. Economically, the product supports the growth of third-party funds (from IDR 3.8 billion in 2022 to IDR 4.5 billion in 2023), but the economic benefits for customers are less significant, as their primary motivation is hajj registration rather than profit sharing. The study recommends enhancing sharia education, transparency, and product innovation to optimize sharia compliance and economic benefits.